Goods versus characteristics: Dimension reduction and revealed preference - Matthew Polisson (Institute for Fiscal Studies (IFS), 2012)
This paper compares the goods and characteristics models of the consumer within a non-parametric revealed preference framework. Of primary interest is to make a comparison on the basis of predictive success that takes into account dimension reduction. This allows us to nonparametrically identify the model which best fits the data. We implement these procedures on household panel data from the UK milk market. The primary result is that the better fit of the characteristics model is entirely attributable to dimension reduction.
Keywords: D11; D12; 330; Characteristics; demand; dimension reduction; nested models; revealed preference